The internal communication plan as an instrument for the implementation of HIV/Aids policy in a hospital - Sunél du Toit; Paul Schutte; Gideon de Wet Gideon de Wet (Communicare, 2022)
This study addresses the internal communication problems of a hospital with regard to the implementation of the HIV/AIDS-policy within a diverse workforce. The research was conducted to determine how well nursing and service health workers at a hospital in North West had been informed about the HIV/AIDS policy of the hospital. It also aimed to determine what suggestions these staff members as well as the staff representatives of each department had as regards the communication and implementation of the HIV/AIDS policy in the hospital. The results of the questionnaires and interviews indicate that the nursing and service health workers of the hospital have poor levels of knowledge of the content of the HIV/AIDS policy and that their communication needs are not met in the implementation of the existing HIV/AIDS policy. Recommendations are made with respect to the development of an internal communication plan to improve the implementation of the HIV/AIDS policy of the hospital.